Efektifitas Foot Exercise and Stretches (FES) terhadap Ankle Brachial Index (ABI) Score dan HbA1c pada Kelompok Penderita DM Tipe 2 - Muhlisoh, Muhlisoh; Hasaini, Asni (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2024)
Diabetes is one of the top 3 causes of death in Indonesia. It is exacerbated by uncontrolled diabetes which affects the body system. Non-pharmacological therapy is highly focused for DMT2 by modifying lifestyle and physical exercise. One of the physical exercises that is easy to do is foot exercise and stretches (FES). The examination carried out to detect blood sugar levels is glycosylated haemoglobin (HbA1c) and for examination of arterial conditions is the ankle brachial index (ABI). The purpose of the study was to analyse the effectiveness of FES on ABI Score and HbA1c in the Type 2 DM Patients Group. The research method is pretest-posttest control group design. The sample size was 20 with 10 intervention group respondents and 10 control group respondents using purposive sampling, FES intervention was given for 5 weeks with a duration of 30 minutes, data analysis using paired t test and independent t test. The results showed that there was a difference in the value of ABI score before and after FES and in the value of HbA1c there was no difference before and after the intervention. This study is expected to encourage the independence of people with DM through physical exercise activities to be able to control arterial conditions in people with DM.